Static and dynamic magnetic properties of Co nanoparticles - Srinath, S.; Poddar, P.; Sidhaye, Deepti S.; Bhagavatula L. V. Prasad; Gass, James; Srikanth, H. (Journal of Nanoscience and Nanotechnology, 2008)
Co nanoparticles have been synthesized using wet-chemical methods. As-synthesized particles show a sharp low temperature peak in zero-field cooled (ZFC) magnetization well below the blocking transition temperature and this feature is associated with surface spin disorder. We have investigated the dynamic magnetic properties of Co using ac susceptibility and resonant RF transverse susceptibility (TS). We also studied the memory and relaxation effects in these nanoparticle systems. From these measurements we show a typical blocking behavior of an assembly of superparamagnetic nanoparticles with a wide distribution of blocking temperatures. The transverse susceptibility measurements on these particles show the presence of anisotropy even above the blocking temperature. The role of surface anisotropy and the size distribution of the particles on the observed memory and magnetic relaxation effects are discussed.
Keywords: Ac Susceptibility; Co Nanoparticles; Magnetic relaxation; Transverse Susceptibility